Quality with equity : the primary education agenda - Education Watch Project (Bangladesh); Ahmed, Manzoor, 1940-; Nath, Samir R.; Hossain, Altaf (Md. Altaf); Campaign for Popular Education (Organization) (Dhaka : Campaign for Popular Education, 2005)
In the Bangladesh context.
"Education Watch report, 2003/04."
Includes statistical tables.
Includes bibliographical references (p. [143]-145) and index.
Includes passages in Bengali.
Keywords: Education, Primary -- Bangladesh -- Evaluation; Education, Primary -- Aims and objectives -- Bangladesh